Price theory and applications - Landsburg, Steven E. 1954- (Cengage Learning, 2014)
Written in the same humorous, reader-friendly style as Professor Landsburg's widely popular trade book, The Armchair Economist, the lively ninth edition of PRICE THEORY AND APPLICATIONS adopts an inductive, hands-on approach that enables students to learn economics by doing. And it requires no knowledge or use of calculus. Using a student-friendly, easy-to-understand format, the book thoroughly develops the standard concepts of intermediate price theory as well as timely, untraditional issues not found in many texts?such as the economics of information. Social welfare is also highlighted as a unifying concept throughout. The book's rigorous, meticulous development of economic theory is supported by countless intriguing and entertaining exhibits, examples, numerical exercises, and problem sets integrated within the text and included at the end of chapters, giving students countless opportunities to test their comprehension of chapter concepts. With its highly interactive approach, the new Price Theory gives students a solid understanding of economic theory as well as the skills to apply it to the world around them.